2022
DOI: 10.1111/tpj.15893
|View full text |Cite
|
Sign up to set email alerts
|

Lateral transfers lead to the birth of momilactone biosynthetic gene clusters in grass

Abstract: SUMMARY Momilactone A, an important plant labdane‐related diterpenoid, functions as a phytoalexin against pathogens and an allelochemical against neighboring plants. The genes involved in the biosynthesis of momilactone A are found in clusters, i.e., momilactone A biosynthetic gene clusters (MABGCs), in the rice and barnyardgrass genomes. In addition, we know little about the origin and evolution of MABGCs. Here, we integrated results from comprehensive phylogeny and comparative genomic analyses of the core ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 65 publications
(134 reference statements)
0
23
0
Order By: Relevance
“…146 Given the evolutionary divergence between rice and especially barnyard grass, as these are separated between the two major clades in the Poaceae plant family, this BGC appears to provide an example of lateral gene transfer. 137,146 However, while nothing is known about the metabolic pathway encoded by the BGC from barnyard grass, it has been shown that at least the CPS and KSL from the relevant wheat BGC exhibits divergent function. 138 Accordingly, this BGC does not appear to have evolved for momilactone production, and not only the identity but also function of the resulting labdane-related diterpenoid remains unclear in the other genera where it is found.…”
Section: Downstream Tailoring/decorating Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…146 Given the evolutionary divergence between rice and especially barnyard grass, as these are separated between the two major clades in the Poaceae plant family, this BGC appears to provide an example of lateral gene transfer. 137,146 However, while nothing is known about the metabolic pathway encoded by the BGC from barnyard grass, it has been shown that at least the CPS and KSL from the relevant wheat BGC exhibits divergent function. 138 Accordingly, this BGC does not appear to have evolved for momilactone production, and not only the identity but also function of the resulting labdane-related diterpenoid remains unclear in the other genera where it is found.…”
Section: Downstream Tailoring/decorating Enzymesmentioning
confidence: 99%
“…By contrast, the Os4BGC exhibits a dramatically broader distribution, with homologous BGCs found in not only other species from the Oryza genus that similarly produce momilactones, 85 but also in barnyard grass ( Echinochloa crus-galli ) 145 and wheat, 138 as well as even more widely throughout the grasses. 146 Given the evolutionary divergence between rice and especially barnyard grass, as these are separated between the two major clades in the Poaceae plant family, this BGC appears to provide an example of lateral gene transfer. 137,146 However, while nothing is known about the metabolic pathway encoded by the BGC from barnyard grass, it has been shown that at least the CPS and KSL from the relevant wheat BGC exhibits divergent function.…”
Section: Biosynthetic Gene Clustersmentioning
confidence: 99%
“…Several lines of evidence suggest that c2BGC plays a more general biosynthetic role, e.g., the production of oryzalexins and oryzalides [ 122 , 123 , 124 ]. Furthermore, it has been shown that the biosynthesis of momilactones requires the contribution of genes belonging to both c4BGC and non-clustered genes located on different chromosomes [ 125 ].…”
Section: Rice Phytoalexin Biosynthesismentioning
confidence: 99%
“…To date, the diterpene synthases OsCPS4 and OsKS4 responsible for the tricyclic momilactone scaffold formation ( Figure 6 ) have been characterized [ 129 , 130 , 131 , 132 ]. These enzymes are encoded by genes clustered with genes encoding cytochrome P450 enzymes (CYPs), CYP99A2 and CYP99A3 , and a short-chain dehydrogenase reductase (SDR), OsMAS , in the biosynthetic gene cluster on rice chromosome 4 (c4BGC) [ 125 ] ( Figure 7 ). This BGC has also been found in the genomes of other Oryza species with AA-genome, namely O. rufipogon and O. punctata , as well as in the distantly related momilactone-producing species Echinochloa crus-galli and Calohypnum plumiforme [ 45 , 113 , 133 ] ( Table 1 ).…”
Section: Rice Phytoalexin Biosynthesismentioning
confidence: 99%
“…With the growing body of genome sequence information available, multiple investigations have been completed to understand the collinear BGC organization within and across species (7)(8)(9). Examples include triterpene thalianols in Arabidopsis thaliana and close relatives, benzylisoquinoline alkaloids in Papaver, steroidal glycoalkaloids in the Solanaceae, triterpene cucurbitacins in the Cucurbitaceae, and momilactone diterpenoids in the grasses (9)(10)(11)(12)(13). Evidence from herbaceous plants showed that complex genetic events such as whole genome duplication (WGD), tandem duplication, gene relocation, chromosomal inversion, lateral gene transfer impact on the assembly, maintaining, and diversi cation of physically clustered and non-homologous, but functionally coordinated genes during the evolutionary process (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%